Improving Reading and Writing Ability of Beginning With The Cooperative Integrated Reading and Composition Method - Siti Maskanah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Reading is an asset for someone to study books and find written information. Reading for a student is also an asset so that they can participate in learning activities. This study aims to improve reading and writing skills beginning with the Cooperative Integrated Reading and Composition (CIRC) learning method. Besides that, it can also improve the ability to read and write at the beginning. This study uses the Cooperative Integrated Reading Composition (CIRC) learning method, this method is one of the integrated cooperative learning methods of reading and writing, where students are divided into several groups to improve their comprehension skills in reading, writing, understanding vocabulary and language arts. This research is able to improve the ability to read and write at the beginning.